Transfer, entanglement and regnal traditions: the mobility of ideas, or how to define princely rank in England and the empire in the fourteenth century - Peltzer, Jörg (European review, 2021)
This paper addresses the theme of mobility in the context of late medieval political thought, more specifically, the rhetoric of royal charters issued in England and the Holy Roman Empire in the fourteenth century.
Published online: 24 April 2020
Gesehen am 01.02.2021